2017
DOI: 10.1097/md.0000000000006885
|View full text |Cite
|
Sign up to set email alerts
|

Eye bank prepared versus surgeon cut endothelial graft tissue for Descemet membrane endothelial keratoplasty

Abstract: The purpose of this article is to examine outcomes of Descemet membrane endothelial keratoplasty (DMEK) performed with cornea bank (CB) prestripped tissue and surgeon stripped tissue (SST).This retrospective study examined subjects who underwent DMEK with CB or surgeon prepared tissue for Fuchs endothelial corneal dystrophy. Best-corrected visual acuity (BCVA), corneal thickness, endothelial cell count (ECC), and complications were examined before and throughout a 6-month postoperative period.Eleven CB and 22 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
14
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 40 publications
0
14
0
1
Order By: Relevance
“…There was no significant difference in CCT and ECD between both groups 6 months after surgery. There was one graft failure with precut tissues and four graft failures with surgeon-cut tissues [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…There was no significant difference in CCT and ECD between both groups 6 months after surgery. There was one graft failure with precut tissues and four graft failures with surgeon-cut tissues [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is commonly thought that surgeons are more prone to perform posterior lamellar techniques when the risk to damage corneal tissue—due to manual preparation—is very low [ 28 , 29 ]. Previous reports have shown no differences in best corrected visual acuity, central corneal pachymetry or complications—dislocations, primary graft failure—found between corneas prepared by the surgeon in the operating room and precut tissue for DSAEK [ 29 – 31 ] or even DMEK [ 32 ]. Other advantages of precut tissue are the lower rate of microbiological culture positivity and lower risk of receptor infection [ 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, it is suggested that a bias of EC count is possible if different methods were used to evaluate the ECD before and after the surgery (Regnier et al. ; Miron et al. ).…”
Section: Discussionmentioning
confidence: 99%